Penerapan Algoritma Bubble Sort Pada Sistem Perpustakaan Menggunakan Framework Codeigniter - Aziz, Toha; Asmiatun, Siti (Information Science and Library, 2022)
SMA IT Bina Amal was founded in 2015, having its address at Jl. Kyai pious No. 8 Semarang ,. Bina Amal Integrated Islamic School has dreams and aspirations for the future of children to get an education that is integral to all aspects of life. One of the efforts is to promote library services. The library of SMA IT BINA AMAL Semarang in managing library administration data still finds many problems that hinder the service process to students. With problems still being found in book data management and a lack of information about books that are often borrowed from the SMA IT BINA AMAL Semarang library, a software that can provide a solution is needed to help librarians in managing library book data and students at SMA IT BINA AMAL Semarang. The results of this study can provide solutions to improve service and performance of librarian in terms of library book data management and accelerate borrowing transactions, returning books by students. And make it easier for students to find out which books are often borrowed, the system is built using the Codeigniter Framework and using the Bubble Sort Algorithm.SMA IT Bina Amal berdiri pada tahun 2015 beralamat di Jl. Kyai saleh No. 8 Semarang,. Sekolah Islam Terpadu Bina Amal memiliki mimpi dan cita-cita masa depan anak-anak mendapatkan pendidikan yang integral mencakup semua aspek kehidupan. Salah satu usahanya adalah memajukan pelayanan perpustakaan. Perpustakaan sekolah SMA IT BINA AMAL Semarang dalam pengelolaan data administrasi perpustakaan masih banyak menemukan masalah yang menghambat proses pelayanan kepada siswa-siswi. Dengan masih ditemukan masalah dalam pengelolaan data buku dan kurangnya informasi mengenai buku yang sering dipinjam pada perpustakaan SMA IT BINA AMAL Semarang maka dibutuhkan suatu perangkat lunak yang bisa memberi solusi untuk membantu petugas perpustakaan dalam mengelola data buku perpustakaan dan siswa di SMA IT BINA AMAL Semarang. Hasil penelitian ini dapat memberi solusi untuk meningkatkan pelayanan dan kinerja petugas perpustakaan dalam hal pengelolaan data buku perpustakaan serta mempercepat transaksi peminjaman, pengembalian buku oleh siswa. Dan mempermudah siswa untuk mengetahui buku yang sering dipinjam, sistem dibangun menggunakan Framework Codeigniter dan menggunkan Algoritma Bubble Sort